Positive Periodic Solution for Second-Order Singular Semipositone Differential Equations - Xiumei Xing (Abstract and Applied Analysis)
We study the existence of a positive periodic solution for second-order singular semipositone differential equation by a nonlinear alternative principle of Leray-Schauder. Truncation plays an important role in the analysis of the uniform positive lower bound for all the solutions of the equation. Recent results in the literature (Chu et al., 2010) are generalized.